Effect of Prebiotic in Commercial Feed on the Growth of Catfish (Pangasius sp.) - Nico Sonyenzellnd; Mustahal Mustahal; Sakinah Haryati (JURNAL PERIKANAN DAN KELAUTAN, 2015)
Length Frequencies of the ladyfish Elops hawaiensis has grouping the ladyfish into the fingerling, young fish and adults fish. The effect of length-weight relationship was negative allometric. This condition revealed that the length growth of the ladyfish more dominant than their weight growth. Analysis of the condition factors showed that the K value was 4.19 for the Kronjo, 4.18 for Mauk and 42.06 for Domas village, respectively. It may be concluded that the environmental factors in the northern coast of Banten Province was suitable for the growth of the ladyfish.